2021
DOI: 10.1101/2021.02.20.21251520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater Monitoring of SARS-CoV-2 from Acute Care Hospitals Identifies Nosocomial Transmission and Outbreaks

Abstract: Background: SARS-CoV-2 has been detected in wastewater and its abundance correlated with community COVID-19 cases, hospitalizations and deaths. We sought to use wastewater-based detection of SARS-CoV-2 to assess the epidemiology of SARS-CoV-2 in hospitals. Methods: Between August and December 2020, twice-weekly wastewater samples from three tertiary-care hospitals (totalling >2100 dedicated inpatient beds) were collected. Wastewater samples were concentrated and cleaned using the 4S-silica column method and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We confirmed this finding by screening the wastewater samples from this study by using a separate assay that targets a D3L mutation in the nucleocapsid gene of the Alpha variant ( 23 ). We quantified total SARS-CoV-2 levels separately with widely used universal assays targeting the N1 and N2 regions of the nucleocapsid gene in the wild-type virus ( 3 , 4 ) and all other VOCs identified to date. We triplexed N200 assays for Omicron, Delta, and total SARS-CoV-2 together so we could estimate an Omicron-to-Delta ratio in each wastewater sample using the Omicron signal (R203K-G204R assay) and the Delta signal (R203M assay) (M. Fuzzen et al, unpub.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed this finding by screening the wastewater samples from this study by using a separate assay that targets a D3L mutation in the nucleocapsid gene of the Alpha variant ( 23 ). We quantified total SARS-CoV-2 levels separately with widely used universal assays targeting the N1 and N2 regions of the nucleocapsid gene in the wild-type virus ( 3 , 4 ) and all other VOCs identified to date. We triplexed N200 assays for Omicron, Delta, and total SARS-CoV-2 together so we could estimate an Omicron-to-Delta ratio in each wastewater sample using the Omicron signal (R203K-G204R assay) and the Delta signal (R203M assay) (M. Fuzzen et al, unpub.…”
Section: Methodsmentioning
confidence: 99%
“…We applied the same method consistently at a given sampling site throughout the entire study period. We processed wastewater samples from 3 (22). We confirmed this finding by screening the wastewater samples from this study by using a separate assay that targets a D3L mutation in the nucleocapsid gene of the Alpha variant (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Omicron and Delta were the only two variants detected in Alberta by clinical screening during the study period (Alberta Health, 2022). Total SARS-CoV-2 levels were quantified with widely used universal assays targeting the N1 & N2 regions of the nucleocapsid gene in the wild type virus (Acosta et al 2021a, b) and all other VOCs identified to date. Omicron, Delta and total SARS-CoV-2 assays were triplexed together enabling an Omicron-to-Delta ratio to be estimated in each wastewater sample using the Omicron signal (R203K-G204R assay) and the Delta signal (R203M assay).…”
Section: Methodsmentioning
confidence: 99%
“…Measuring levels of RNA from SARS-CoV-2 in sewage samples began being used as a complementary surveillance tool early in the pandemic, resulting in hundreds of wastewater COVID-19 monitoring groups and online dashboards around the world (Naughton et al 2021), including in Alberta (https://covid-tracker.chi-csm.ca). This strategy is premised on the fecal shedding of SARS-CoV-2 by infected individuals (Cevik et al 2021; Yuan et al 2021) and enabled by modifying RT-qPCR workflows used for diagnosing patients to quantify viral RNA in sewage sampled at wastewater treatment plants (WWTPs) or other nodes within the sewer network (Acosta et al 2021a, b; Qiu et al 2022) at regular intervals. Teams in Alberta and elsewhere demonstrated during pandemic waves that wastewater is a leading indicator of COVID-19, with results typically preceding clinical diagnosed cases by 4-6 days (e.g., D’Aoust et al 2021, Medema et al 2020; Nemudryi et al 2020; Randazzo et al 2020).…”
Section: Introductionmentioning
confidence: 99%